2021
DOI: 10.3847/1538-4357/abf63d
|View full text |Cite
|
Sign up to set email alerts
|

The Changing-look Blazar B2 1420+32

Abstract: Blazars are active galactic nuclei with their relativistic jets pointing toward the observer, comprising two major subclasses, flat-spectrum radio quasars (FSRQs) and BL Lac objects. We present multiwavelength photometric and spectroscopic monitoring observations of the blazar B2 1420+32, focusing on its outbursts in 2018–2020. Multiepoch spectra show that the blazar exhibited large-scale spectral variability in both its continuum and line emission, accompanied by dramatic gamma-ray and optical variability by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 75 publications
2
21
0
Order By: Relevance
“…However, these standard unification pictures for the difference between these classes meet challenges after the discovery of 'Changing-look' AGNs or blazars. The shifting between Type I AGNs and Type II AGNs was observed and reported (Matt et al 2003;Bianchi et al 2005;Marchese et al 2012;Shappee et al 2014), and the shifting was also reported between FSRQs and BL Lacs (Isler et al 2013(Isler et al , 2015Mishra et al 2021).…”
Section: Comparing With 'Changing-look' Blazars In Previous Workmentioning
confidence: 54%
See 1 more Smart Citation
“…However, these standard unification pictures for the difference between these classes meet challenges after the discovery of 'Changing-look' AGNs or blazars. The shifting between Type I AGNs and Type II AGNs was observed and reported (Matt et al 2003;Bianchi et al 2005;Marchese et al 2012;Shappee et al 2014), and the shifting was also reported between FSRQs and BL Lacs (Isler et al 2013(Isler et al , 2015Mishra et al 2021).…”
Section: Comparing With 'Changing-look' Blazars In Previous Workmentioning
confidence: 54%
“…The classification types, which based on the optical spectrum of AGNs and that of blazars were harmonious until the discovery of 'Changing-look' AGNs (Matt et al 2003;Bianchi et al 2005). The shifting between Type I AGNs and Type II AGNs, or the shifting between FSRQs and BL Lacs has brought great challenges to the AGN unification model (Marchese et al 2012;Shappee et al 2014;Isler et al 2013;Mishra et al 2021;Peña-Herazo et al 2021). There are explanations for the shifting, among them the sudden change of accretion ratio arising the shift seems promising.…”
Section: Introductionmentioning
confidence: 99%
“…How much extend FeII emission region is under debate, but it is likely comparable to the dust sublimation radius (e.g., He et al 2021;Mishra et al 2021;Gaskell et al 2022). The typical sublimation radius is ∼ 100 light days (Namekata & Umemura 2016), but the typical difference in observation epoch in Analysis 3 is ∼ 1, 000 days.…”
Section: Distribution On the Ev1 Planementioning
confidence: 99%
“…With the term changing-look AGN (CLAGN), we refer to those sources that can change their classification (e.g., from BLLAC to FSRQ or vice versa) after some dramatic event, such as a change in the accretion or in the jet activity [28][29][30][31][32][33]. Sometimes the jet activity can determine changes in the observational appearance but not a change in classification: for example, the decrease/increase of equivalent width of the emission lines when the continuum increases/decreases because of the jet activity [34][35][36][37] or a shift of the synchrotron peak [38,39].…”
Section: Classificationmentioning
confidence: 99%